Chloe. 3, Frenemies - Tessier, Greg (Charmz, 2018)
Chloe should be on top of the world, but her nemesis Anissa crashes her new internship and her BF is moving away, putting her in a dark mood. She meets a new social group and her old friends and family wonder if she can pull herself out of her funk or whether she will succumb to the depression.